On a new amphipod: Iphimedia eblanae - Bate, [C.] S. (The Natural History Review, 1857)
The author's name appears as "Spence Bate" on the first page, "W. Spence Bate" on p. 299 (explanation of the figures) and "C. Spence Bate" on the plate itself.
Ant'Phipoda Literature database